Luminescence - emerging new applications - Chávez García, Dalia H.; Guzmán Jiménez, Mario H. (IntechOpen, 2024)
ABSTRACT Nanomaterials offer promising solutions for chemotherapy challenges, addressing issues like cytotoxicity and biocompatibility. In cancer clinical protocols, biomedical imaging is vital, providing insights into tumor morphology. Luminescent nanomaterials or nanoparticles (LNPs), particularly effective for diseases like cancer, possess controllable properties like size (usually <100 nm), surface charge, and external functionalization. LNPs interact with biological systems at systemic and cellular levels. Cellular uptake is crucial, allowing selective targeting of cancer cells through overexpressed surface receptors such as transferrin receptor (TfR), G-protein coupled receptor (GPCR), folate receptor (FR), epidermal growth factor receptor (EGFR), lectins, and low-density lipoprotein receptor (LDLR). LNPs can accumulate in subcellular compartments, playing a pivotal role in drug delivery. Studies explore LNPs’ internalization into cells, investigating their potential to deliver cargoes like DNA, siRNA, miRNA, and small-molecule drugs. This review highlights the latest advancements in LNPs and their biomedical applications. Despite these promising developments, comprehensive nanotoxicological assessments are crucial for a better understanding of LNPs’ behavior in biological systems, paving the way for future clinical applications. RESUMEN Los nanomateriales ofrecen soluciones prometedoras para los desafíos de la quimioterapia, abordando cuestiones como la citotoxicidad y la biocompatibilidad. En los protocolos clínicos del cáncer, las imágenes biomédicas son vitales, ya que proporcionan información sobre la morfología del tumor. Los nanomateriales o nanopartículas luminiscentes (LNP), particularmente eficaces para enfermedades como el cáncer, poseen propiedades controlables como tamaño (normalmente <100 nm), carga superficial y funcionalización externa. Las LNP interactúan con sistemas biológicos a nivel sistémico y celular. La captación celular es crucial, ya que permite dirigirse selectivamente a las células cancerosas a través de receptores de superficie sobreexpresados, como el receptor de transferrina (TfR), el receptor acoplado a proteína G (GPCR), el receptor de folato (FR), el receptor del factor de crecimiento epidérmico (EGFR), las lectinas y las células cancerosas bajas. -receptor de lipoproteínas de densidad (LDLR). Las LNP pueden acumularse en compartimentos subcelulares, desempeñando un papel fundamental en la administración de fármacos. Los estudios exploran la internalización de las LNP en las células, investigando su potencial para entregar cargas como ADN, ARNip, miARN y fármacos de molécula pequeña. Esta revisión destaca los últimos avances en LNP y sus aplicaciones biomédicas. A pesar de estos avances prometedores, las evaluaciones nanotoxicológicas integrales son cruciales para comprender mejor el comportamiento de las LNP en sistemas biológicos, allanando el camino para futuras aplicaciones clínicas.
Upconversion Luminescent Nanoparticles and Their Biomedical Applications in Imaging
https://doi.org/10.5772/intechopen.1005378
Keywords: Rare earth; Upconversion luminescent; Near-infrared; Biological imaging; Nanotoxicological assessment; Campus Ensenada